2014
DOI: 10.1128/jcm.00909-14
|View full text |Cite
|
Sign up to set email alerts
|

Comamonas kerstersii and the Perforated Appendix

Abstract: We read with interest two recent reports of Comamonas kerstersii-related infections in the abdomen (1) and bloodstream (2). We wish to add our own experience with C. kerstersii-related abdominal infections.Case 1. A 10-year-old boy presented with a 1-day history of abdominal pain. Examination revealed peritonitis in the right iliac fossa. On admission, his white blood cell count was 10.3 ϫ10 9 / liter and his C-reactive protein level was 228 mg/liter. A diagnosis of appendicitis was made, and an open appendect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 4 publications
0
25
0
4
Order By: Relevance
“…The data of a few foreign studies of the antimicrobial susceptibility testing of C. kerstersii strains do not allow comparison of the results, as some authors used a disc-diffusion method (not recommended by CLSI) for testing these microorganisms [8] or testing using other interpretation criteria [4,5]. Nevertheless, the MIC results allow us to conclude that resistance to fluoroquinolones, trimethoprim/ sulfamethoxazole and amikacin was noted among C. kerstersii strains isolated at different times [4,5,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data of a few foreign studies of the antimicrobial susceptibility testing of C. kerstersii strains do not allow comparison of the results, as some authors used a disc-diffusion method (not recommended by CLSI) for testing these microorganisms [8] or testing using other interpretation criteria [4,5]. Nevertheless, the MIC results allow us to conclude that resistance to fluoroquinolones, trimethoprim/ sulfamethoxazole and amikacin was noted among C. kerstersii strains isolated at different times [4,5,17].…”
Section: Discussionmentioning
confidence: 99%
“…In the UK for two years, C. kerstersii were isolated from 27 hospitalized patients with diarrhea. The authors suggested that the carriage of this microorganism in the intestine can occur more often than was previously thought, since modern identification methods were not available [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current literatures supported that Comamonas spp. was related to infections including phlegmon, peritonitis, endocarditis, meningitis, septicemia and UTI (Cooper et al, 2005;Biswas, Fitchett & O'Hara, 2014;Horowitz et al, 1990). Barua et al (2017) found that nephritic syndrome patients with higher serum cholesterol were more susceptible to UTI than those with normal serum cholesterol, which might be because high cholesterol concentrations suppress lymphocyte function.…”
Section: Discussionmentioning
confidence: 99%
“…The current literatures supported that Comamonas spp. was related to infections including phlegmon, peritonitis, endocarditis, meningitis, septicemia, and UTI (Cooper et al, 2005;Biswas et al, 2014;Horowitz et al, 1990). Barua et al found that nephritic syndrome patients with higher serum cholesterol were more susceptible to UTI than those with normal serum cholesterol, which might be because high cholesterol concentrations suppress lymphocyte function (Barua et al, 2016 Manuscript to be reviewed (Rochelson et al, 2007;Weglicki et al, 1992), and a previous rodent model study demonstrated that magenesium-deficiency elevated circulating levels of inflammatory cytokines (Weglicki et al, 1992).…”
Section: Discussionmentioning
confidence: 99%